Minangkabau Customary Law as a Foundation and Perspective for The Formation of The National Legal System - Wiwoho, Shri Hardjuno; Saptomo, Ade; Ilham, Andi Muh; Santoso, Haryo (Syntax Corporation, 2024)
The purpose of this study is to examine the role of Minangkabau customary law in shaping the country's legal system and its potential contribution in creating social justice, maintaining cultural diversity, and strengthening regional autonomy. This research method used is literature analysis using relevant primary and secondary sources such as legal documents, academic works, and practical experience in the application of Minangkabau customary law. The results of this study show that Minangkabau customary law includes interrelated principles such as deliberation and consensus, gon royong (community cooperation), and restorative justice. The principles contain universal values that can be applied and integrated into the broader national legal system. In the context of building a state legal system, Minangkabau customary law is used as a source of inspiration for the development of laws that serve the interests of local communities, protect individual and collective rights, and maintain a balance between national and local interests. In addition, Minangkabau customary law has the potential to preserve cultural diversity in Indonesia. In the era of globalization that prioritizes cultural homogenization, the application of Minangkabau customary law can provide a strong foundation for the development and maintenance of cultural diversity of the community at the national level. Through an approach that respects and recognizes cultural differences, a country's legal system can be a tool for strengthening cultural identity and ensuring the sustainability of valuable cultural heritage